Phenological variability drives the distribution of wildfires in Sardinia - Angelis, Antonella; Bajocco, Sofia; Ricotta, Carlo (Landscape Ecology, 2012)
Fuel characteristics play an important role in driving ﬁre ignition and propagation; at the landscape scale fuel availability and ﬂammability are closely related to vegetation phenology. In this view, the NDVI proﬁles obtained from high temporal resolution satellites, like MODIS, are an effective tool for monitoring the coarse-scale vegetation seasonal timing. The aim of this paper is twofold: our ﬁrst objective consists in classifying by means of multitemporal NDVI proﬁles the coarse-scale vegetation of Sardinia into ‘phenological clusters’ in which ﬁre incidence is higher (preferred) or lower (avoided) than expected from a random null model. If ﬁres would burn unselectively, then ﬁres would occur randomly across the landscape such that the number of ﬁres in a given phenological cluster would be nearly proportional to the relative area of that land cover type in the analyzed landscape. Actually, certain vegetation types are more ﬁre-prone than others. That is, they are burnt more frequently than others. In this framework, our second objective consists in investigating the temporal parameters of the remotely sensed NDVI proﬁles that best characterize the observed phenology–ﬁre selectivity relationship. The results obtained show a good association between the NDVI temporal proﬁles and the spatio-temporal wildﬁre distribution in Sardinia, emphasizing the role of bioclimatic timing in driving ﬁre regime characteristics.
Keywords: Clustering; Fire selectivity; Image segmentation; MODIS; NDVI proﬁles; Residuals